A cost-effectiveness analysis of screening for intracranial aneurysms in persons with one first-degree relative with subarachnoid haemorrhage. (December 2016) - Hopmans, Esther M; Ruigrok, Ynte M; Bor, Anne SE; Rinkel, Gabriel JE; Koffijberg, Hendrik
Introduction: Although persons with one first-degree relative with aneurysmal subarachnoid haemorrhage have an increased risk of aneurysm formation and aneurysmal subarachnoid haemorrhage, screening them for unruptured intracranial aneurysms was not beneficial in a modelling study from the 1990s. New data on the risk of aneurysmal subarachnoid haemorrhage in these persons and improved treatment techniques call for reassessment of the cost-effectiveness of screening. Patients and methods: We used a cost-effectiveness analysis using a Markov model and Monte Carlo simulation comparing screening and preventive aneurysm treatment with no screening in persons with one first-degree relative with aneurysmal subarachnoid haemorrhage. We analyzed the impact on quality-adjusted life years, costs and net health benefit of single screening (at varying screening age) and serial screening (with varying screening age and intervals) using a cost-effectiveness threshold of €20, 000/quality-adjusted life year. Results: In 17 of the 24 strategies assessed, additional costs for screening for unruptured intracranial aneurysm were <€20, 000 per quality-adjusted life year gained. The strategy with highest net health benefit was screening at age 40 and 55. Screening every five years from age 20 to 70 yielded the highest health benefits at the highest additional costs. Discussion: Based on current risks of aneurysmal subarachnoid haemorrhage and complications of preventive treatment, several strategies to screen for unruptured intracranial aneurysm in persons with one first-degree relative with aneurysmal subarachnoid haemorrhage are cost effective compared with no screening, when applying a cost-effectiveness threshold of €20, 000/quality-adjusted life year. Conclusion: We recommend discussing with persons at risk the option of screening twice, at age 40 and 55, which will result overall in substantial health benefits at acceptable additional costs.